EVALUATION OF CHEMICAL CONCENTRATIONS FOR LIQUID MEDICAL WASTE (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Health waste is defined as infectious or hazardous medical or biological waste that, due to its properties, leads to or contributes significantly to an increase in mortality or serious diseases that are permanent or disabled. They also pose a potential risk to human health or the environment when improperly treated, stored, transported, disposed of or managed. Therefore, the research dealt with important chemical analyzes of liquid medical waste for a public health center and a specialized dental center over a period of six months of the year to fully identify how to treat this waste and the efficiency of treatment units. The results showed that the concentrations of chemical analyzes for the health center are higher than the concentrations recorded for the dental center. The acidity function and the phosphate ion are somewhat acceptable during the specified months. Sulfate and electrical conductivity were high in the sixth month of the year. A significant increase in the concentrations of biological requirement on oxygen (BOD), which represents the amount of oxygen needed by microorganisms to break down organic matter, as well as a significant increase in the chemical requirement for oxygen (COD), which represents the concentration of organic matter indirectly. This indicates the presence of high bacterial contamination that needs to be treated and followed